MOSSBAUER INVESTIGATIONS AND MOLECULAR ORBITAL CALCULATIONS ON EPIDOTE - Grodzicki M.; Heuss-Assbichler S.; Amthauer G. (My University, 2001)
The electronic structure of iron-rich epidote has been investigated by cluster molecular orbital calculations in local spin density approximation. Calculated quadrupole splittings for Fe(III) at both the M1 and M3 sites are in quantitative agreement with the experimental values obtained by Mossbauer spectroscopy. A detailed analysis of the theoretical results shows that a strong tetragonal compression of the M3 octahedron is responsible for the unusually large value of the quadrupole splitting of FeM3I). The corresponding electric field gradient (efg) is dominated by the anisotropy of the valence shell of iron, whereas the ligands contribute only about 15% to the efg. The calculations emphasize that rather large clusters, extending beyond the second coordination sphere of iron, are necessary for a reliable description. Small clusters including only the first coordination sphere of iron generally yield misleading results due to unsaturated oxygen bonds and relatively large cluster charges.
Keywords: EPIDOTE; MOLECULAR ORBITAL CALCULATIONS; MOSSBAUER SPECTROSCOPY